Analysis of Competition Levels, Pricing, and Human Resources on the Competitiveness of Small Contractors - Restu Meihadi; Budi Susetyo (Green Publisher Indonesia, 2025)
The construction industry in Indonesia makes a significant contribution to the national economy, occupying the fourth position with a contribution of 10.06% according to BPS (2024). More than 77% of construction business entities are classified as small contractors, which leads to a high level of competition in this sector. To survive, small contractors need to implement strategies to increase Competitiveness through efficiency, innovation, and quality improvement. This study aims to identify effective strategies in increasing the competitiveness of small contractors in building construction projects. The results showed that the Competition Level variable (X1) did not have a significant direct influence on Competitiveness (Y), with a T-statistic of 0.509 and a P-value of 0.611. In contrast, Price Quotation (X2) and Human Resources (Z) were shown to have a significant direct influence, with T-stats of 2,917 and 4,710 and P-values of 0.004 and 0.000, respectively. However, in the moderation test, Human Resources was unable to strengthen the relationship between the level of competition and the price offer to competitiveness because the resulting T-statistical value was smaller than the T-table and the P-value was above 0.05, so it can be concluded that although HR is directly important, its role as a moderator is not significant in this study.